Physical – chemical quality of arid soil in onion (allium cepa l.) With a soils bioenhancer and organic fertilizers in majes irrigation - Omar Zeballos Cáceres (2017)
The present trial was carried with the aim to evaluate the effect of a soils bioenhancer and organic fertilizers on the physical and chemical component of quality soil in onion in Majes Irrigation. The trial was carried out in a plot under spray irrigation and splot under drip irrigation, in both plot was stablished the sources and levels from organic fertilizer (Chicken manure and seabird guano) compared against chemical fertilization. A completely random block design was used with 9 treatments and 3 repetitions for each plot, after that it was made a combined analysis to both plots. Effective deep roots and average infiltration speed were evaluated like physical indices of quality soils. The electric conductivity, pH, CaCO3 (%), organic matter (%) phosphorus (ppm), potassium (ppm), cation exchange capacity and exchangeable cations (Ca, Mg, Na y K), were evaluated like chemical indices of quality soils. The effective deep roots did not show significantly statics different. Chicken manure and seabird guano treatments applied with bioenhancer; show the higher average infiltration speed than treatments with only applications of bioenhancer and the treatment without organic fertilizer, this were significantly statics different. Treatments applied only with bioenhancer and seabird guano tend to reduce CaCO3 (%) and pH. Chicken manure and seabird guano treatments show the higher average available phosphorus, this were significantly statics different from the rest of treatments. Exchangeables cations and organic matter did not show significantly statics different among treatments. Drip irrigation showed to have greater values of electric conductivity and cation exchange capacity, this were significantly statics different.